Taxonomy and distribution of Cylindera germanica (Linnaeus, 1758) in the Middle East with the description of two new subspecies (Coleoptera, Carabidae, Cicindelinae) - Boetzl, Fabian A.; Franzen, Michael (Zootaxa, 2020)
Two new tiger beetle taxa, Cylindera germanica erzincana ssp. nov. Boetzl & Franzen, 2020 from eastern Anatolia and Cylindera germanica persiana ssp. nov. Boetzl & Franzen, 2020 from southern Iran are described based on morphological characters. We present the current knowledge on the distribution of C. germanica (Linnaeus, 1758) in the Middle East and present a first record of C. germanica muelleri (Magistretti, 1966) for Turkey. An identification key for the subspecies of C. germanica occurring in the Middle East is provided.